Homogenisasi Budaya dan Pengaruh Teknologi: Korean Wave Sebagai Budaya Global - Nickasari Hendytami; Najamuddin Khairur Rijal; Devita Prinanda (Jurnal Noken: Ilmu-Ilmu Sosial, 2022)
Korean Wave or Hallyu is a trend that has developed in the world in the last thirty years. This article discusses the development of the Korean Wave as a form of cultural homogenization facilitated by technology until it is adopted as a global culture. The type of this research is descriptive with a qualitative approach. Data was collected through internet based research. The results show that the spread of the Korean Wave as a form of cultural homogenization is strongly influenced by technology. This can be seen by the dominance of the Korean Wave not only in Asia, but also in Europe, America, and even the Middle East from the use of the internet and social media. This shows that the Korean Wave has been adopted as a global culture.